2006
DOI: 10.1063/1.2206183
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniversality of commonly used correlation-energy density functionals

Abstract: The correlation energies of the helium isoelectronic sequence and of Hooke's atom isoelectronic sequence have been evaluated using an assortment of local, gradient and meta-gradient density functionals. The results are compared with the exact correlation energies, showing that while several of the more recent density functionals reproduce the exact correlation energies of the helium isoelectronic sequence rather closely, none is satisfactory for Hooke's atom isoelectronic sequence. It is argued that the unifor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…In 35, we have combined the Overhauser equations with the KS equations in a self‐consistent way, recovering full CI total energies within 1 mH for the He isoelectronic series. In 34, we have shown that, unlike all the available correlation functionals 36, the model works equally well for the high‐density limit of the He and the Hooke's atom series. Thus, on one hand, the Overhauser model seems to be a very good candidate to construct short‐range correlation energy functionals.…”
Section: Introductionmentioning
confidence: 93%
“…In 35, we have combined the Overhauser equations with the KS equations in a self‐consistent way, recovering full CI total energies within 1 mH for the He isoelectronic series. In 34, we have shown that, unlike all the available correlation functionals 36, the model works equally well for the high‐density limit of the He and the Hooke's atom series. Thus, on one hand, the Overhauser model seems to be a very good candidate to construct short‐range correlation energy functionals.…”
Section: Introductionmentioning
confidence: 93%
“…24 Remarkably, we found that it is feasible to choose parameters for the Wigner functional such that the correlation energies for the helium isoelectronic sequence are estimated adequately. 24 Remarkably, we found that it is feasible to choose parameters for the Wigner functional such that the correlation energies for the helium isoelectronic sequence are estimated adequately.…”
Section: Reparametrization Of Wigner's Functionalmentioning
confidence: 90%
“…Attempting to identify such characteristics, we evaluated the expectation values ͗1/r͘, ͗r͘, and ͗r 2 ͘ for both the exact and the Hartree-Fock ground states. 24 To test how well scaling with a screened Z performs, we evaluated ͗1/r͘ / ͑Z − ͒ with the above scaling factors. 2-4, respectively.…”
Section: A Procedures To Determine Wigner Parametersmentioning
confidence: 99%
“…Some of the acomplishments and shortcomings of this assortement of approximate functionals has been recently reviewed. 18,40 We provide in what follows some arguments showing that the functional F [ρ] is not universal.…”
Section: The Non-universal Character Of F [ρ] In Hks-dftmentioning
confidence: 99%